China's New Strategic Layout - Xin, Ming (China Insights,, 2018)
This book, based on the Chinese dream and its basic principles, global significance, path of implementation and practical requirements, systemically explains China's Four-Pronged Comprehensive Strategy. The Four-Pronged Comprehensive Strategy is the strategic concept of the Communist Party of contemporary China. In the coming five and even the fifty years, the economic and social development of the Chinese society will be centering on it. Comprehensively constructing a moderately prosperous society is the strategic goal, comprehensively deepening reform and advancing the law-based governance of China are the engine and guarantee in realizing the strategic goal, while strengthening the Party Self-discipline represents the strategic measures to build up a firm core leadership. The Four-Pronged Comprehensive Strategy shows not only the CPC's view of China but also the view of world.